Structural Characteristics of the Lens in Presenile Cataract - Andjelic, Sofija; Drašlar, Kazimir; Hvala, Anastazija; Hawlina, Marko (Frontiers in Medicine, 2021)
The purpose of this work is to examine the structure of the anterior lens epithelial cells (aLECs) of presenile idiopathic cortical cataract to investigate the possible structural reasons for its development. The anterior lens capsules (aLCs: basement membrane and associated lens epithelial cells) were obtained from routine uneventful cataract surgery of 5 presenile cataract patients (16 and 41 years old women and 29, 39, and 45 years old men). None of the patients had family history of cataract, medication, or trauma and they were otherwise healthy. In addition, the patients did not have any other abnormal features in the ocular status except cataract. The aLCs were prepared for scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The most prominent abnormal features observed by SEM for all 5 studied presenile cataract patients were the changes of the aLECs structure with the dents, the selective concavity of some LECs, at their apical side centrally toward the nucleus. In addition, TEM showed the thinning of the lens epithelium with the segmentally concave cells and the compressed and elongated nuclei. Abnormal and distinguishable structural features were observed in the anterior lens epithelium aLECs in all 5 patients with presenile cataract. Disturbed structure of aLECs, regularly present in presenile cataract type is shown that might be associated with water accumulation in the presenile idiopathic cortical cataract lens.